Cutaneous carbonyl stress is associated with nerve dysfunction in recent-onset type 2 diabetes - Bönhof, Gidon Josia; Strom, Alexander; Jung, Tobias; Bódis, Kálmán B.; Szendrödi, Julia; Wagner, Robert; Grune, Tilman; Roden, Michael; Ziegler, Dan (Diabetes care, 2024)
Endogenous carbonyl stress leads to the formation of advanced glycation end products (AGEs). AGEs represent a potential target to prevent or treat diabetic sensorimotor polyneuropathy (DSPN). The current study aimed to characterize cutaneous carbonyl stress, oxidative stress, immune cells, and endothelial cell damage in early type 2 diabetes compared with normal glucose tolerance (NGT) using novel cutaneous biomarkers.Included were 160 individuals recently (≤12 months) diagnosed with type 2 diabetes and 144 with NGT from the German Diabetes Study baseline cohort. Nerve function was assessed using electrophysiological, quantitative sensory, and clinical testing. Skin biopsies were obtained to analyze intraepidermal nerve fiber density, AGE autofluorescence, argpyrimidine area, and endothelial cell area. In addition, skin autofluorescence was measured noninvasively using the AGE reader. A subgroup with type 2 diabetes (n = 80) was reassessed 5 years later.After adjustment for sex, age, HbA1c, LDL cholesterol, and BMI, argpyrimidine area (17.5 ± 18.8 vs. 11.7 ± 12.7%) was higher in recent-onset type 2 diabetes than in NGT (P < 0.05). AGE autofluorescence was inversely correlated with nerve conduction (e.g., peroneal motor nerve conduction velocity: r = −0.346) and positively with AGE reader measurements in type 2 diabetes (r = 0.358, all P < 0.05), but not in NGT. Higher baseline AGE autofluorescence and lower endothelial cell area predicted the deterioration of clinical and neurophysiological measures after 5 years.Cutaneous AGE markers were associated with neurophysiological deficits in recent-onset type 2 diabetes and predicted their progression after 5 years, substantiating the role of carbonyl stress in the development of early DSPN.
Gesehen am 22.09.2025